Repurchase Options in the Market for Lemons - Bigio, Saki; Shi, Liyan (Review of Economic Studies, 2026)
Abstract We study repurchase options (repo contracts) in a competitive asset market with adverse selection. Gains from trade emerge from a liquidity need, but private information about asset quality prevents the full realization of trades. In equilibrium, a single repo contract pools all assets. The embedded repurchase option mitigates adverse selection by improving the volume of trades relative to outright sales. However, liquidity provision can be inefficiently low as lenders compete to attract high-quality assets via high haircuts and low rates. The equilibrium has a closed form and aligns well with empirical patterns across Mortgage-Backed Securities repos.